1975
DOI: 10.1083/jcb.67.3.835
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of proteins across membranes. I. Presence of proteolytically processed and unprocessed nascent immunoglobulin light chains on membrane-bound ribosomes of murine myeloma.

Abstract: Fractionation of MOPC 41 DL-I tumors revealed that the mRNA for the light chain of immunoglobulin is localized exclusively in membrane-bound ribosomes. It was shown that the translation product of isolated light chain mRNA in a heterologous protein-synthesizing system in vitro is larger than the authentic secreted light chain; this confirms similar results from several laboratories. The synthesis in vitro of a precursor protein of the light chain is not an artifact of translation in a beterologous system, beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
1,152
4
8

Year Published

1981
1981
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 2,930 publications
(1,202 citation statements)
references
References 34 publications
38
1,152
4
8
Order By: Relevance
“…In other eukaryotic cells, proteins destined for export enter the secretory pathway by co-translational translocation across the ER membrane mediated by the recognition of a N-terminal signal peptide and concomitant cleavage of this signal peptide by the signal peptidase complex (SPC) [16]. It has been assumed that P. falciparum proteins exported to the host RBC have their ER-type signal peptides cleaved by the parasite SPC but this type of N-terminal processing has never been definitively characterized.…”
Section: Introductionmentioning
confidence: 99%
“…In other eukaryotic cells, proteins destined for export enter the secretory pathway by co-translational translocation across the ER membrane mediated by the recognition of a N-terminal signal peptide and concomitant cleavage of this signal peptide by the signal peptidase complex (SPC) [16]. It has been assumed that P. falciparum proteins exported to the host RBC have their ER-type signal peptides cleaved by the parasite SPC but this type of N-terminal processing has never been definitively characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Signal peptides serve as a sorting signal that targets nascent secretory proteins to sites of translocation on the ER membrane, where it is subsequently proteolytically removed from the mature chain by signal peptidase. 27,28 Signal peptides do not contain specific amino-acid residues and are variable in length (15 to as many as 50 amino acids). Kaiser et al 29 reported that many random sequences can functionally replace the secretion signal sequence of yeast invertase.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, targeting of newly synthesized proteins to mitochondria seems to follow a general principle of intracellular protein traffic, that is the presence of signal sequences on the proteins to be transported across membranes and the existence of complementary structures on the surface of organelles which recognize the preproteins belonging to the respective cellular subcompartment (Milstein et al, 1972;Blobel & Dobberstein, 1975).…”
Section: Abstract: Mitochondrial Receptor Complex--general Insertionmentioning
confidence: 99%